THE IMPACT OF INTANGIBLE FACTORS IN SHAPING THE IDENTITY OF ANCIENT CITIES AND ARCHITECTURE OF CHINA - Kelly, Tamara (PLANNING MALAYSIA, 2017)
China is an immense nation and highest population on earth with incredible civilization, it kept up its character over millenniums in spite of its different ethnic gatherings and distinctive geographical conditions. The Ancient Chinese architecture and urban planning are fundamental units of the world architecture and well known of their particular character. In addition, they were an extraordinary wellspring of motivation for some neighbouring nations. Several factors were behind the momentous Chinese architecture and urban planning, and among those was the emperor guidance who unified the government and encouraged regularity in many aspect in Chinese architecture including city planning. The aim of this paper is to examine the impact of nonphysical factors such as Chinese culture and beliefs in shaping the distinct identity of ancient Chinese cities. This is done by studying; feng shui notion, Yin and Yan forces, the theory of five elements and other Metaphysics philosophies of China. Furthermore, this paper scrutinises a number of Chinese ancient capital cities and temples of heaven in Beijing as case studies to measure to what extent the intangible factors contributed in shaping the identity and layout of Chinese cities and architecture.